(untitled) (Med Phoenix, 2017)
Ayurveda, an orthodox as well as main stream system of medicine has been with a source of new concepts and products for healthcare. Euphorbia hirta Linn. (EH) is an advantageously authenticated medicinal plant as observable from the literature. Rural and tribal people of India use different parts of this plant to surmount various diseases. Its use in traditional medicine has been assured on scientific basis by studying pharmacology of the plant in vitro and in vivo Information was collected from different data base resources. MED Phoenix Volume (1), Issue (1) July 2016, page: 31-38